2004
DOI: 10.1095/biolreprod.103.024067
|View full text |Cite
|
Sign up to set email alerts
|

Different Regulatory Pathways of Endometrial Connexin Expression: Preimplantation Hormonal-Mediated Pathway Versus Embryo Implantation-Initiated Pathway1

Abstract: Transformation of the endometrium into the receptive phase is under the control of ovarian steroid hormones and is modulated by embryonic signals during implantation. We have previously shown that this differentiation process is accompanied by a suppression of gap junction connexins (Cx) 26 and 43 before implantation followed by a local induction of both connexins in the implantation chamber. In the present study, we demonstrate that connexin gene expression in the rodent endometrium is regulated via two disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 63 publications
(81 reference statements)
4
33
0
2
Order By: Relevance
“…Recently we have shown that conditional loss of expression of Cx43, a major gap junction component in uterine stromal cells, impairs decidualization and angiogenesis during early pregnancy (6). The uterine expression of Cx43 is regulated by E (22). It is therefore conceivable that the local E produced by the aromatase in the decidua controls Cx43 expression, which in turn contributes to the progression of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently we have shown that conditional loss of expression of Cx43, a major gap junction component in uterine stromal cells, impairs decidualization and angiogenesis during early pregnancy (6). The uterine expression of Cx43 is regulated by E (22). It is therefore conceivable that the local E produced by the aromatase in the decidua controls Cx43 expression, which in turn contributes to the progression of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…used implantation marker in murine models and localized distinctively in implantation/placental loci [27][28][29][30], this marker was used to assess the spatial distribution of LRSC during gestation (GD7, 14) and the early postpartum (PPD1) period. The connexin 43 expression was restricted to the implantation/ placental loci of the gestational endometrium (Fig.…”
Section: Stem/progenitor Cells In Mouse Endometrium Awaken After Partmentioning
confidence: 99%
“…Implantation of mammalian embryos in the uterus occurs in the so-called receptive phase, during which steroid hormones and local embryonic signals suppress the expression of endometrial Cx26 and Cx43. Later, connexin expression is locally reinduced by the implanting blastocyst, presumably as a result of factors secreted by the growing throphoblast (184,185,186). Ovariectomized rats treated with different ratios of 17␤-estradiol and progesterone revealed a dose-and timedependent regulation of the expression of Cx26 (the main connexin of the endometrial epithelium) and Cx43 (the prominent connexin of uterine stroma and myometrium) but not Cx32, indicating that hormonal ratios mimicking pregnancy conditions differentially regulate ␣-and ␤-type connexins (185).…”
Section: Hormonal Control Of Connexin Expressionmentioning
confidence: 99%
“…During preimplantation, this induction is due to estrogens, via the activation of a pathway initiated at ␣-estrogen receptors. However, during the subsequent embryo implantation and decidualization, endometrial connexins are upregulated by an estrogen receptor-independent pathway, possibly implicating catechol estrogen, prostaglandin F 2␣ , and interleukin-1␤ (184). LH and follicle-stimulating hormone control the coupling of ovarian thecal cells, by regulating Cx43 expression at the transcriptional, translational, and posttranslational levels (178).…”
Section: Hormonal Control Of Connexin Expressionmentioning
confidence: 99%